Data Mining Rekomendasi Sekolah Calon Siswa SMA di Kota Tomohon Menggunakan Metode K-Means Clustering - Civita Loho; Vivi Peggie Rantung; Gladly Caren Rorimpandey (JOINTER : Journal of Informatics Engineering, 2022)
Tomohon is a small city in North Sulawesi. In Tomohon City, there are 12 high schools and the equivalent that are officially registered on the reference data site of the Ministry of Education and Culture.in practice, the number of students enrolled in 12 schools in each academic year has a significant difference. This is influenced by the high public perception of schools that are labeled ‘favorite schools’ with other schools. This study aims to group data on prospective high school students in Tomohon City for the 2021/2022 academic year using the K-Means Clustering method for high school recommendations. K-Means is a partition-based Clustering method in Data Mining where data will be grouped based on the level of similarity, so that student data that have the same characteristics are grouped into one cluster, while student data with different characteristics are grouped into different clusters.